Spontaneous Complete Remission of Acute Myeloid Leukemia in the Absence of Disease-Modifying Therapy following Severe Pulmonary Involvement by Coronavirus Infectious Disease-19 - Barkhordar, Maryam; Rostami, Fatemeh Tajic; Yaghmaie, Marjan; Abbaszadeh, Mehrdad; Chahardouli, Bahram; Mousavi, Seied Asadollah (Case Reports in Hematology, 2022)
Coronavirus infectious disease-19 (COVID-19) usually alters the innate and adaptive immune setting by excessive production of proinflammatory cytokines, leading to a deviation in the natural course of simultaneous malignant disease. In the absence of disease-modifying therapy, complete remission of acute myeloid leukemia (AML) is an extraordinary event caused mainly by an immune-related mechanism secondary to a severe infectious process. We present a 57-year-old woman with a new diagnosis of AML associated with a 11q23/KMT2A abnormality who had achieved temporary spontaneous remission in the absence of disease-modifying therapy following the severe pulmonary infection with coronavirus lasting for six months. We review the literature and explain the potential impact of stimulated immune responses by COVID-19 on induction of remission in a patient with AML that could provide an excellent opportunity for new immune-based therapies to evolve for the hematologic malignancies. Despite the high ability of the immune process to destroy the malignant cells, the remission of duration is usually short. Therefore, it seems that continuing treatment after SR of AML by a consolidation regimen or bone marrow transplantation, based on a risk-adapted treatment approach, may reduce the recurrence risk.